2023
DOI: 10.1177/19417381231160167
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes After ACL Reconstruction in Soccer (Football, Futbol) Players: A Systematic Review and Meta-Analysis

Abstract: Context: The risk factors for anterior cruciate ligament (ACL) tear for athletes participating in pivoting sports includes young age and female sex. A previous meta-analysis has reported a reinjury rate of 15% after ACL reconstruction (ACLR) for athletes across all sports. To the best of the authors’ knowledge, this is the first systematic review and meta-analysis of available literature reporting outcomes after ACLR in soccer players. Objective: To review and aggregate soccer-specific outcomes data after ACLR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 76 publications
0
5
0
Order By: Relevance
“…ACL and cartilage tissue reconstruction are surgical procedures often performed in soccer players for knee injuries. The knee plays a crucial role as one of the most vital joints in a soccer player's body and damage to the ACL or cartilage tissue can result in limited mobility and force the player to stop his sports career [36][37][38]. In this pilot study effects of follow-up after Hyalofast scaffold cartilage surgery combined with ACL reconstruction in the case of a professional athlete were presented.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ACL and cartilage tissue reconstruction are surgical procedures often performed in soccer players for knee injuries. The knee plays a crucial role as one of the most vital joints in a soccer player's body and damage to the ACL or cartilage tissue can result in limited mobility and force the player to stop his sports career [36][37][38]. In this pilot study effects of follow-up after Hyalofast scaffold cartilage surgery combined with ACL reconstruction in the case of a professional athlete were presented.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, amidst the controversies surrounding the approach and selection of cartilage defect treatments, one undeniable fact remains: certain lesions necessitate repair to prevent further deterioration. Preserving the integrity and functionality of the affected joint is paramount, and appropriate treatment interventions are imperative to achieve this goal [38].…”
Section: Discussionmentioning
confidence: 99%
“…The anterior cruciate ligament (ACL) is commonly injured during sports activities, and ACL reconstruction (ACLR) is the current standard surgical treatment to regain knee joint stability and improve knee function 1 4 . Despite remarkably improved clinical outcomes following ACLR 5 , several recent studies reported that some patients still have difficulty returning to pre-injury sports participation levels after isolated ACLR 6 10 , possibly due to rotational knee instability at high levels of activity 11 . The addition of anterolateral ligament reconstruction (ALLR) to ACLR recently emerged as a potential solution 11 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Finally, a systematic review and meta-analysis revealed that soccer players experienced high ACL injury rates after primary ACL reconstruction and demonstrated similar reinjury rates, consistent with previous literature of athletes who participated in high-demand pivoting sports. [ 9 ]…”
mentioning
confidence: 99%